UTILIZATION OF SMARTPHONES AS HUMAN MACHINE INTERFACE DISPLAYS FOR CONVEYOR CONTROL SYSTEMS LOGO BASED! WEB SERVER - Kartika Kartika; Asran Asran; Bambang Harianto (RADJA PUBLIKA, 2022)
This study discusses the use of smartphones as a Human Machine Interface (HMI) display on a conveyor control system with web server technology that has been embedded in the PLC LOGO!.On average, all industrial conveyor control and monitoring systems are HMI-based which are displayed on a large monitor screen. This of course has its own saturation for operators in controlling and monitoring the conveyor because it just sits in one place.The application of smartphones as HMI displays on conveyor control systems can overcome this because the small size of the smartphone can be held, practical and can be carried everywhere. The HMI display application is built using web server technology with the main control being PLC LOGO! Siemens seriesLOGO!0BA8 and a wi-fi network generating device in the form of an outdoor point to point CPE type 01. The input data is taken from the conveyor safety device component which is processed by the PLC and sent to a web server that can be accessed by smartphones via a private IP address.Based on the results of this study, the use of smartphones as HMI displays on conveyor control systems with LOGO! web server technology is able to read input values from conveyor safety devices, and can control to turn on and turn off the conveyor motor at a distance of the outdoor point to point CPE scope.